Sobre o Rio... - 2015 - Luiza Pires, Ana; Pessoa, Ana; Éleres, Isadora; Meirelles, Mariana; Teixeira, Mariana; Vidal, Mariana; das Neves, Monique; -, Nabylla (POLÊM!CA, 2015)
Coletânia de fotos sobre o Rio